2014
DOI: 10.1038/srep04757
|View full text |Cite
|
Sign up to set email alerts
|

Superior Tensile Ductility in Bulk Metallic Glass with Gradient Amorphous Structure

Abstract: Over centuries, structural glasses have been deemed as a strong yet inherently ‘brittle’ material due to their lack of tensile ductility. However, here we report bulk metallic glasses exhibiting both a high strength of ~2 GPa and an unprecedented tensile elongation of 2–4% at room temperature. Our experiments have demonstrated that intense structural evolution can be triggered in theses glasses by the carefully controlled surface mechanical attrition treatment, leading to the formation of gradient amorphous mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…A question is then raised: How could we extend the local plastic deformation into the macroscopic tensile plasticity rather than the brittle fracture governed by a thin main SB? Recent work showed that the macroscopic tensile plasticity could be obtained by introducing the artificial micro-structural defects, such as the notches [15,16], the surface indentations [17], the designing hole array [18] and laser shock peening treatment [19]. These results indicate that the formation of multiple SBs and the stable propagation of main SBs are the two key factors for improving the tensile plasticity of BMGs.…”
Section: Introductionmentioning
confidence: 81%
“…A question is then raised: How could we extend the local plastic deformation into the macroscopic tensile plasticity rather than the brittle fracture governed by a thin main SB? Recent work showed that the macroscopic tensile plasticity could be obtained by introducing the artificial micro-structural defects, such as the notches [15,16], the surface indentations [17], the designing hole array [18] and laser shock peening treatment [19]. These results indicate that the formation of multiple SBs and the stable propagation of main SBs are the two key factors for improving the tensile plasticity of BMGs.…”
Section: Introductionmentioning
confidence: 81%
“…However, in tension, the tensile stress enhances softening and instability, a dominant shear band slips without obstacle, and bulk and micro-sized MGs fracture elastically 3 . Various approaches have been introduced to retard the dominant shear band to improve tensile ductility of bulk and micro-sized MGs, such as designing MG matrix composites 4,5 , sharp-and-deep notches 6 , laminating MG with ductile crystalline metals 7,8 , surface mechanical treatment 911 , laser surface texturing treatment 12 , and MG-based chiral nanolattice 13 . In addition, size reduction approach changes room temperature plastic deformation mechanism of MG from shear banding into homogeneous plastic flow 1418 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the constrained stress field such as compression and bending, considerable plastic in BMGs can be achieved by multiple shear bands [10e14]. Based on this mechanism, substantial efforts have been made to enhance the tensile ductility of MGs, such as introducing heterostructures [15], notching [16,17], surface treatment [18,19] and cold working [20]. Nevertheless, the flow is still constrained in shear band and the ductility is also carried by multiple shear bands.…”
Section: Introductionmentioning
confidence: 99%